Studies at the level of light and electron microscopy the connection of perlslnusoldal cells with vitamin a, lipid metabolisms and fatty liver syndrome in hens - Reşat Nuri AŞTI (Eurasian Journal of Veterinary Sciences)
The purpose of this study was to investigate at the level of light and electron microcopy the connection of perisinusoidal cells with Vitamin A, lipid metabolism and fatty liver syndrome in hens. Forty adult Bobcock breed hens were used throughout the study. Examination of control animals' liver tissue revealed few perisinusoidal cells carrying one or two smail lipid droplets in their cytoplasms. In the animals subcutanely administrated with Vitamin A palmitat, it was determined that the number of perisinusoidal cells and of lipid droplets in the cytoplasm of these cells were increased lipid droplets in the epithelial cells had not changed. In the third group animals fed with high energy rations, histopathological features of fatty liver syndrome were observed.Epithelial cells of the liver tissue filled with big and smal lipid droplets.lt was determined that the number of perisinusoidal cells and of lipid droplets of these cells had not changed. On the other hand characteristic histopathological findings of fatty liver syndrome were sean in the hepatic cells of hens fed with high energy rations and given Vitamin A palmitat. In addition, together with the increase in the number of lipid droplets enumeration of perisinusoidal cells have multiplied. According to our findings. lt was concluded that perisinusoidal cells of liver are related with Vitamin A metabolism. However these cells did not participate in the formatian of fatty liver syndrome and lipid metabolism.